Relationship Between People Social Support and Achievement Motivation With Reading Interest in Junior High School Students in D.I. Yogyakarta - Lina Kartika Sari (Psycho Holistic, 2021)
This study aims to determine; 1) the relationship between peer social support and students' reading interest; 2) the relationship between achievement motivation and students' reading interest; 3) the relationship between peer social support and achievement motivation with students' reading interest. This study involves one dependent variable, namely reading interest and two independent variables that influence it, namely peer social support and achievement motivation. The research subjects were 92 junior high school students in the D.I. Yogyakarta, which consists of 41 male students and 51 female students. The research method used is a quantitative approach with a measuring instrument for reading interest scale, peer social support scale, and achievement motivation scale. The data analysis used assumption test and hypothesis test. The research hypothesis test used product-moment correlation to test the first and second hypotheses, while the third hypothesis was analyzed using multiple linear regression. The results of the product-moment correlation analysis showed that there was a positive relationship between peer social support and student interest in reading (r=0.472; p<0.01) and there was a positive relationship between achievement motivation and student interest in reading (r=0.680; p<0.01). Based on multiple linear regression analysis, there is a positive relationship between peer social support and achievement motivation together with reading interest in students (r=40,835; p<0.01). The contribution of peer social support and achievement motivation with reading interest in junior high school students in Yogyakarta is ​​0.479 or 47.9% explained by the variables of peer social support and reading interest, while the remaining 52.1% is explained by the other variable.